Combined steam and CO2 reforming of methane over carbon-resistant boron-promoted Ni/SBA-15 catalysts for syngas production - Tan, Ji Siang (2018)
Combined steam and CO2 reforming of methane (CSCRM) has recently appeared as a promising technique since it is capable of generating a green and sustainable energy source from biogas. In fact, CSCRM is reportedly a promising reforming process owing to its high catalytic stability in the coexistence of CO2 and H2O oxidizing reactants and flexible adjustment of H2/CO ratios by the manipulation of feedstock composition. Ni-based catalysts are widely known encountering barriers of coke formation and Ni metal sintering lead to rapid catalyst deactivation at high reaction temperature. Hence, the aim of this research was to investigate the effect of B-promoter on the physicochemical properties of 10%Ni/SBA-15 catalyst and examine the influence of reaction temperature and reactant partial pressure on the catalytic performance of CSCRM reaction. The unpromoted and B-promoted 10%Ni/SBA-15 catalysts were prepared by sequential incipient wetness impregnation method and assessed for combined steam and CO2 reforming of methane (CSCRM) at various reaction temperatures of 973-1073 K and stoichiometric feed composition. An inevitable decline in BET surface area and average NiO crystallite size with boron promotion from 1% to 5%B loading could be due to the agglomeration of B2O3 particles and deboration reaction during calcination and hence blocking mesopores of SBA-15 support at elevated B composition. NiO particles were reduced completely to metallic Ni0 phase during H2 pretreatment and the reduction temperature of NiO phase was shifted towards higher temperature with B-addition due to enhancing interaction between the basic NiO and acidic B2O3 phases. For all reaction temperature employed, 3%B appeared to be the best promoter loading in terms of reactant conversions and 3%B-10%Ni/SBA-15 catalyst exhibited the highest H2 yield of 69.4% at 1073 K. The CH4 and CO2 conversions were enhanced about 23.2% and 32.4%, correspondingly with rising reaction temperature from 973 to 1073 K due to its endothermic nature. Additionally, the effect of various feed composition on CSCRM was also investigated in order to obtain the optimum feed ratio. The increase in CO2 partial pressure from 15 to 25 kPa resulted in a decline in both CH4 and CO2 conversions probably due to the competing adsorption between reactants. In addition, the decline in CO2 conversion and the increase in CH4 conversion at H2O partial pressure greater than 20 kPa could suggest that steam reforming of methane was more preferable than CO2 reforming of methane reaction. The reducing reactant conversions with rising CH4 partial pressure could suggest that the rate of carbon formation via CH4 deposition was superior to that of carbon gasification by CO2 and oxidizing agents in CH4-rich feedstock. From the above results, the of 15 kPa, of 20 kPa and of 45 kPa appeared to be the best feed composition for the CSCRM reaction in terms of reactant conversions and product yields. Interestingly, irrespective of operating parameters, the H2/CO ratio was always varied within 1.1 to 2.6 appropriate for downstream Fischer-Tropsch synthesis. The 3%B-10%Ni/SBA-15 catalyst appeared to be stable for 24 h on-stream at stoichiometric feed composition and reaction temperature of 973 to 1073 K in terms of catalytic activity and product yield. The 3%B- 10%Ni/SBA-15 catalyst exhibited the lowest degree of catalyst deactivation could be assigned to the promotional effect of boron addition. Boron promoter suppressed the formation of graphitic carbon on catalyst surface and the amount of carbonaceous deposition was reduced about 4 times.